Creación de una planta de acopio de cacao, procesamiento y exportación de pasta de cacao. - Jarrín Bourgeat, Patricio (2017)
The change in the productive matrix demands new production alternatives that allow the industrialization of products so that they acquire greater value in the international markets. Ecuador is a country that enjoys important advantages that allow it to produce high quality primary goods. Cocoa is one of them, being necessary the production of derivatives like the cocoa that is required by several industries. Therefore, the main objective of the present investigation is to analyze the feasibility of its production, for which an administrative, technical and operational survey has been carried out, which allowed us to conclude that the activity is profitable and must be executed. The study methodology used included qualitative and quantitative studies, which allowed to have vital information to support each one of the strategies presented, giving rise to a structure properly directed to reach important levels of profitability. The proposal in addition to generating profitability produces direct and indirect sources of employment which contribute to the national economic development and the improvement of the living conditions of the population in general. In this way, the generation of added value is promoted in traditional products, being a base to recover a positioning of leadership in the national market based on fine aroma cocoa and pulp production.